2020
DOI: 10.1186/s42480-019-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Process intensification technologies for CO2 capture and conversion – a review

Abstract: With the concentration of CO 2 in the atmosphere increasing beyond sustainable limits, much research is currently focused on developing solutions to mitigate this problem. Possible strategies involve sequestering the emitted CO 2 for long-term storage deep underground, and conversion of CO 2 into value-added products. Conventional processes for each of these solutions often have high-capital costs associated and kinetic limitations in different process steps. Additionally, CO 2 is thermodynamically a very stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 158 publications
0
46
0
Order By: Relevance
“…In addition to fuels, chemicals such as ethylene, alcohols, formic acid (or formate), syngas, urea and other organic materials can be produced from CO 2 , electrochemically, thermo-chemically or by other approaches [323,[329][330][331][332][333][334][335][336][337]. Such organic chemicals are often more expensive than fuels and may offer advantages in the techno-economic analysis.…”
Section: Co 2 Utilizationmentioning
confidence: 99%
“…In addition to fuels, chemicals such as ethylene, alcohols, formic acid (or formate), syngas, urea and other organic materials can be produced from CO 2 , electrochemically, thermo-chemically or by other approaches [323,[329][330][331][332][333][334][335][336][337]. Such organic chemicals are often more expensive than fuels and may offer advantages in the techno-economic analysis.…”
Section: Co 2 Utilizationmentioning
confidence: 99%
“…Much better intensification levels can be obtained by the combination of materials, methods and equipment, or two or more technologies in a given process. 42,43 Many kinds of adsorbents are utilised in adsorptive separations, such as activated carbon, zeolites and carbon molecular sieves. However, they might be associated with low adsorption capacities towards an adsorbate especially at large-scale processing.…”
Section: Pi On Adsorptive Separation Applicationsmentioning
confidence: 99%
“…So, many efforts have been devoted to means to further improve the performance of various adsorbents. 43 In this study, emerging applications of PI on adsorptive separations as an innovative approach in recent years were considered, and the selected trends were identified with comparison in terms of the applied adsorption technology, intensification technique and the achieved process enhancements. Selected PI studies from the literature for different cases of adsorption separations are shown in Table 2.…”
Section: Pi On Adsorptive Separation Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1, we provide a summary of the latest review/perspective papers to highlight the major scientific and industrial interests in this field since 2018. As can be noted, a diversity of intensified and modular technologies are being investigated to address the dual challenge of energy productivity/efficiency and environmental sustainability, 30 for example, reactive distillation, 24 intensified reactors, 15 alternative energy sources, 14 and advanced materials 33 . Another rapidly emerging research theme is computer‐aided process intensification 11,32 .…”
Section: Introductionmentioning
confidence: 99%